John Lakenheath's rearrangement of the archives of Bury St Edmunds Abbey, c. 1380 - Dunning, ANJ (Oxford University Press, 2018)
John Lakenheath (d. 1381) was a monk and administrator of the estates of Bury St Edmunds Abbey. He reorganized its archives in 1378–81, still in disorder after it had been sacked by the townspeople in 1327. This culminated in the ‘Lakenheath Registry’ (London, British Library, MS Harley 743), an indexed directory of the Bury charters created in 1379–81. His preface to this book explains the archive’s mode of operation, and is here printed for the first time and translated.